The Mom Test: How to talk to customers & learn if your business is a g ood idea when everyone is lying to you - Fitzpatrick, Rob (CreateSpace Independent Publishing Platform, 2023)
The Mom Test is a quick, practical guide that will save you time, mone y, and heartbreak.They say you shouldn't ask your mom whether your bus iness is a good idea, because she loves you and will lie to you. This is technically true, but it misses the point. You shouldn't ask anyone if your business is a good idea. It's a bad question and everyone wil l lie to you at least a little . As a matter of fact, it's not their r esponsibility to tell you the truth. It's your responsibility to find it and it's worth doing right .Talking to customers is one of the foun dational skills of both Customer Development and Lean Startup. We all know we're supposed to do it, but nobody seems willing to admit that i t's easy to screw up and hard to do right. This book is going to show you how customer conversations go wrong and how you can do better.